Challenges and Progress in improving Safety and Managing Radioactive Wastes at Chornobyl NPP and in the Chornobyl Exclusion Zone - Molitor, N.; Drace, Z.; Bugai, D.; Sizov, A.; Haneke, K.; Thierfeldt, S.; Nitzsche, O.; Shapiro, Y. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
The commissioning of the New Safe Confinement at the Chornobyl Nuclear Plant Unit 4 site will mark the achievement of one important milestone within the process “conversion of the Chornobyl Unit 4 into safe ecologic conditions”. New radioactive waste management facilities have been developed at Chornobyl Nuclear Plant and at Vektor Complex to ensure the safe management of radioactive wastes in the Chornobyl Exclusion Zone. The continued investigations and safety assessments of different legacy waste sites which were created as part of the accident response measures confirm the efficiency of the measures of the past are and consolidate the basis for the strategy for the safe management of legacy wastes. All these together demonstrates that the national and international efforts vested to manage the consequences of the Chornobyl accident have achieved substantial and visible progress in safety and long term safety will be achieved by their consistent continuation.